The Vandal habrosýne and its Significance in Procopius’ Narrative on the Rise and Fall of the Vandal State - Stachura, Michał (Studia Ceranea, 2024)
The description of the Vandals’ habrosýne (Procopius, De bellis, IV, 6, 5–9) apparently fit in with the topos of “a nation once valiant who, living among the luxuries, succumbed to effeminacy”, which had been present in Greco-Roman literature since the time of Herodotus. Following such a course of interpretation, this description could explain why the once formidable conquerors were so easily defeated by a comparatively smaller force under Belisarius’ command. However, a closer look at the actual function of this passage in Procopius’ narrative on the rise and fall of the Vandal state brings this seemingly obvious interpretation into question. It gains a particular significance when we discover some surprising parallels between the fates of the last Vandal king, Gelimer, and the last Lydian king, Croesus – as these two are depicted by Procopius and Herodotus, respectively. If we should recognize that what we have here is a particular literary allusion, a re-application of a Herodotean pattern for the purpose of recounting a contemporary story, this passage takes on a new meaning: representing the former affluence and the present misery of the Vandals serves as a starting point to deliberations on human helplessness in the face of Fate, while referring to habrosýne, as a stereotypical characteristic attributed to the Lydians, is an additional clue to put us on a track leading to associations between the two narratives.